P116Rip promotes myosin phosphatase activity in airway smooth muscle cells. Issue 1 (25th July 2019) - Komatsu, Satoshi; Wang, Lu; Seow, Chun Y.; Ikebe, Mitsuo
Abstract: Myosin phosphatase‐Rho interacting protein (p116 Rip ) was originally found as a RhoA‐binding protein. Subsequent studies by us and others revealed that p116 Rip facilitates myosin light chain phosphatase (MLCP) activity through direct and indirect manners. However, it is unclear how p116 Rip regulates myosin phosphatase activity in cells. To elucidate the role of p116 Rip in cellular contractile processes, we suppressed the expression of p116 Rip by RNA interference in human airway smooth muscle cells (HASMCs). We found that knockdown of p116 Rip in HASMCs led to increased di‐phosphorylated MLC (pMLC), that is phosphorylation at both Ser19 and Thr18. This was because of a change in the interaction between MLCP and myosin, but not an alteration of RhoA/ROCK signaling . Attenuation of Zipper‐interacting protein kinase (ZIPK) abolished the increase in di‐pMLC, suggesting that ZIPK is involved in this process. Moreover, suppression of p116 Rip expression in HASMCs substantially increased the histamine‐induced collagen gel contraction. We also found that expression of the p116 Rip was decreased in the airway smooth muscle tissue from asthmatic patients compared with that from non‐asthmatic patients, suggesting a potential role of p116 Rip expression in asthma pathogenesis. Abstract : In this study, we demonstrated that p116Rip regulates the association of myosin phosphatase with myosin for the control of the phosphorylation of myosin regulatory light chain that determines the actomyosin‐based contractile activity of the human airway smooth muscle cells (HASMCs).